Penyuluhan mengenai pencegahan kebutaan akibat katarak di Puskesmas Merdeka Palembang - Amin, Ramzi; Maya Sari, prima; salim, muhammad usman; nindita, dezca (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Unoperated cataracts and uncorrected refractive errors are the most common causes of visual impairment worldwide. Currently, around 94 million elderly people in the world (50 years and above) experience visual impairment or blindness that could be addressed through access to cataract surgery. The Community Ophthalmology Team from the Department of Ophthalmic Health at the Faculty of Medicine, Sriwijaya University, conducted an educational program aimed at enhancing participants' understanding of cataracts, with the goal of increasing awareness regarding prevention and improving community readiness for surgical intervention. A total of 45 participants, who are patients at Puskesmas Merdeka, engaged in the educational session effectively. The participants demonstrated high enthusiasm during the question-and-answer session, and observations indicated an improvement in their knowledge about cataracts. This educational program successfully enhanced public understanding of cataracts and preventive measures.